NEW VIEWS ON THE ACTIVITY OF KHOJA AHROR VALI - Mirzabakhrom Botirov (Journals Park Publishing, 2023)
In the article has been analyzed new views on the activity of Khoja Ahror Vali and studying the period of the Timurids, give a high assessment to the role and position of individual governors in the life of the country, and describe the activities of religious leaders and entire social groups one-sidedly. Besides, article has showed such a reaction to the activities of the Naqshbandiyya sect and its leaders was characteristic by historical sources.
Keywords: Timurids, Khoja Ahror, Muslim, individual governors, Naqshbandiyya, socio-cultural identity.